2016
DOI: 10.1002/lt.24494
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplant outcomes using ideal donation after circulatory death livers are superior to using older donation after brain death donor livers

Abstract: Multiple reports have demonstrated that liver transplantation following donation after circulatory death (DCD) is associated with poorer outcomes when compared with liver transplantation from donation after brain death (DBD) donors. We hypothesized that carefully selected, underutilized DCD livers recovered from younger donors have excellent outcomes. We performed a retrospective study of the United Network for Organ Sharing database to determine graft survivals for patients who received liver transplants from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 25 publications
0
42
0
Order By: Relevance
“…Based on the published literature, strict recommendations for the acceptance or refusal of potential liver donors cannot be made. The authors concluded that careful donor organ and recipient selection can lead to excellent results[14]. …”
Section: Discussionmentioning
confidence: 99%
“…Based on the published literature, strict recommendations for the acceptance or refusal of potential liver donors cannot be made. The authors concluded that careful donor organ and recipient selection can lead to excellent results[14]. …”
Section: Discussionmentioning
confidence: 99%
“…(3) We know that ideal DCD livers, ie, those from donors aged <50 years and with cold ischemia time <6 hours, provide superior graft survival compared with DBD livers from donors older than 60 years. (4) We also know, that in the United Kingdom, accepting a DCD liver for a given recipient provides a significant survival benefit compared with waiting on the list for a DBD liver. (5) These data strongly support the utilization of DCD livers for LT.…”
Section: See Article On Page 397mentioning
confidence: 99%
“…26 Accordingly, investigators from the University of Wisconsin recently published that, compared with older DBD donors (> 60 y old), graft survival after DCD liver transplant was superior when the DCD donor was young (< 50 y old) and when the DCD liver cold ischemia times were minimized. 26 However, DCD liver transplant outcomes overall were observed to be worse than for DBD liver recipients. These findings suggest that DCD livers should not be turned down in favor of older DBD livers.…”
Section: Improvements Over Timementioning
confidence: 99%
“…In addition, acceptance of these livers (many are currently discarded) could add many trans plantable organs to the donor pool. 26 …”
Section: Improvements Over Timementioning
confidence: 99%